A meta-analysis on the geographical distribution and prevalence of parasitic nematodes infecting cattle in four top cattle-producing countries of Asia - Cagurangan, Elizabeth Paige R. (Animo Repository, 2023)
With the demand for cattle expected to increase in Asia, the scale of cattle farming is also expected to increase. A majority of cattle are raised in small-scale setups, with cattle being raised by families as a form of savings. This form of cattle management may put the livestock at a higher risk of parasitic infections due to the lack of veterinary care and regulations. The purpose of this study is to identify the most prevalent parasitic nematode in four top-cattle producing countries of Asia; namely India, Pakistan, Indonesia, and Bangladesh. The study also investigates the association of certain factors with the prevalence of these parasites such as climate type, sex, and age. This study was conducted as a meta-analysis, using One-way Analysis of Variance (ANOVA) to identify the most prevalent nematode and to determine the association of climate type with the identified nematodes from these four countries. Chi-square test was also used to determine the association between sex and prevalence of nematodes, and age and prevalence of nematodes. Strongyles was the most prevalent nematode in India (23.1%), Pakistan (3.32%), and Indonesia (12.5%) while Toxocara spp. was the most prevalent in Bangladesh (14.3%). Köppen-Geiger climate types have been shown to have no significant statistical difference (p > 0.05) to nematode prevalence. Sex and age have also been determined to have a significant difference (p < 0.05) in terms of nematode prevalence. The high prevalence of strongyles suggests the need for an integrated parasite management approach that would improve the control of nematode infection in these countries. The lack of association between the climate types and nematodes suggests the need for further investigations that focus on other environmental factors in Asian countries. Significant associations of sex and age with nematode prevalence call for further investigation into factors that influence these associations.